Pemberdayaan Kader dalam Meningkatkan Kesehatan Melalui Pelatihan Berbasis Kearifan Lokal di Desa Tegalweru Kecamatan Dau Kabupaten Malang - Desy Dwi Cahyani; Sheila Tania M; Asworoningrum Yulindahwati (Idea Pengabdian Masyarakat, 2022)
The empowerment of women in the health sector can be categorized as one type of health development. The form of women's empowerment can be in the form of processing materials using the potential of local materials that have value. The target of this community service activity is the health cadres of Tegalweru Village, Dau, Malang Regency, as many as 20 people. This community service activity is carried out in the form of counseling and demonstrations as well as training for mothers with the lecture method, question, and answer, pre-test, post-test, and practice. The implementation of Community Service Activities went well with an increase in the average knowledge before and after being given counseling about the health benefits of oranges. In addition, the cadres were also very enthusiastic about the practice of making suction pudding made from oranges and orange peel tea. The provision of counseling can empower cadres who initially do not know to know. Besides that, training on making pudding and orange peel is also very useful for cadres who initially still cannot process existing local wisdom into being able to process them into appropriate materials. Keywords: author guidelines, a medical journal, article template describes the scope of the study and the terms of the underlying implementation research.